2020
DOI: 10.1093/nsr/nwaa288
|View full text |Cite
|
Sign up to set email alerts
|

Regulating off-centering distortion maximizes photoluminescence in halide perovskites

Abstract: Metal halide perovskites possess unique atomic and electronic configurations that endow them with high defect tolerance and enable high-performance photovoltaics and optoelectronics[1–3]. Perovskite light-emitting diodes have achieved an external quantum efficiency of over 20%[4–5]. Despite tremendous progress, fundamental questions remain, such as how structural distortion affects the optical properties. Addressing their relationships is considerably challenging due to the scarcity of effective diagnostic too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(56 citation statements)
references
References 40 publications
4
52
0
Order By: Relevance
“…For the past few years, interest in high‐pressure research on halide perovskite materials has increased significantly. [ 16–18 ] Various pressure effects have been observed in halide perovskites, such as band gap modulation, pressure‐induced emission, [ 19–22 ] piezochromism, [ 23,24 ] and metallization. [ 25–27 ] The common features of photoluminescence (PL) of halide perovskites under high pressure are summarized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…For the past few years, interest in high‐pressure research on halide perovskite materials has increased significantly. [ 16–18 ] Various pressure effects have been observed in halide perovskites, such as band gap modulation, pressure‐induced emission, [ 19–22 ] piezochromism, [ 23,24 ] and metallization. [ 25–27 ] The common features of photoluminescence (PL) of halide perovskites under high pressure are summarized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…We expect these lone-pair driven structural instabilities discovered in CsMBr 3 also prevail in their organic HP counterparts, which are more widely used in photovoltaics. 76…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated that an optimal distortion in metal halide perovskites is preferred to determine the PIE. [ 26,28–30 ] In addition, Li et al. reported an irreversible phase transition of acetamidinium nitrate by introducing CH 3 to impart steric hindrance, thus increasing the potential barrier of phase transition to stabilize the high‐pressure phase.…”
Section: Introductionmentioning
confidence: 99%